'Mzungu!': implications of identity, role formation and programme delivery in the sport for development movement. Issue 3 (2nd July 2016) - Manley, Andrew; Morgan, Haydn; Atkinson, Joshua
Abstract : Prevailing academic notions regarding Sport-for-Development-and-Peace (SDP) programmes advocate a 'transformative vision' that is hoped to convert the movement from a 'damaging' development practice, to one which fulfils its potential and elicits benefits worldwide. Volunteers are perceived to be a fundamental element of this transformative vision. This paper provides insight into the voluntary experience of the SDP movement, placing particular attention towards notions of self, the (re)construction of identity and its impact upon the delivery of a developmental initiative located within a Zambian community. Utilizing an interactionist perspective, the paper identifies three related themes that collectively represent the experiential landscape across which participant views were aired – preconceptions and effect on identity and behaviour; experiences and effect on identity and behaviour; and responses to experiences of identity disruption. Following analysis of these themes, the paper finds that SDP programmes may be enhanced through increased transparency of communication in relation to the role of the volunteer to limit preconceptions and expectations associated with the programme and enable volunteers to arrive in the field better equipped to respond to the challenges of the role.